Performance of red gypsum as cement replacement in mortar - Tony, Chong Soon Fung (2014)
More than 400 hundred tons of red gypsum (RG) has been produced in Bukit Besi,Terengganu every year. Currently, the utilization of industrial by product in mortar or concrete is priority due to environmental and economical concerned. The goal of this study is to investigate the perfornance of the Red Gypsum as cement replacement in mortar. There are 4 different mixtures of RG weight proportions were prepared and tested (0%, 5%, 10%, 15%). All specimens were cured in water and air at 3,7,14, and 28 days. The density, compressive strength, water absorption and porosity values were recorded. The results showed that 5% of the RG mixture is nearest and a comparable result with the control specimen. The replacement of cement with RG in the mortar mixture leads to reduction of the industrial waste deposit to the landfill. With the reduction of cement usage there would be less release of CO2 into the atmosphere in equivalent proportion. The usage of waste material will also reduce the cost of the project.